Syirkah Model For Islamic Gold Monetization - Hardiansyah, Hardiansyah (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study proposes a syirkah model for gold monetization as a product innovation opportunity alternative in Islamic Financial Institutions (IFI) towards bullion bank activity implementation because of Act of Law No. 4 of 2023 about P2SK. A descriptive qualitative approach was used in this study of fiqh literature from Shariah Standard No. 57 on gold trading and its trading control released by the World Gold Council and AAOIFI, as well as Fatwa DSN MUI for Musharakah contract. This study was also validated by semi-structured interviews. To clearly define the originality, we use simulation to present and compare the concept with an existing gold-based pawn contract (Ar-Rahnu). Risk-adjusted calculation to protect the initial value. The result shows that this syirkah model can be an alternative to productive gold investment.